Gender and Age Differences in the Relationship Between Smartphone Addiction and Sleep Duration in Korean Children: A Panel Quantile Regression Study - Jeong K; Cho S; Song D; Li R; Han S; Cho HJ; Kim J (Psychology Research and Behavior Management)
Kyuhyoung Jeong,1 Sunghwan Cho,2 Dohun Song,1 Ruonan Li,1 Sangyoon Han,3 Heeran J Cho,4 Jongho Kim5 1Department of Social Welfare, Jeonbuk National University, Jeonju, Jeonbuk-do, Republic of Korea; 2Department of Social Welfare, The Catholic University of Korea, Bucheon, Kyeonggi-do, Republic of Korea; 3Department of Social Welfare, Semyung University, Jecheon, Chungcheongbuk-do, Republic of Korea; 4Department of Public Health Administration, Seoul Cyber University, Seoul, Seoul, Republic of Korea; 5National Catholic School of Social Service, The Catholic University of America, Washington, DC, USACorrespondence: Sunghwan Cho, Email scho9595@catholic.ac.krPurpose: This study analyzed the longitudinal relationship between smartphone addiction and sleep duration to investigate the factors contributing to sleep deprivation in Korean children.Methods: To overcome the limitations of previous studies, panel quantile regression analysis was used to evaluate the relationship between smartphone addiction and sleep duration. Key variables were smartphone addiction, sleep duration, gender, and age.Results: According to the study results, the level of smartphone addiction among children significantly increased from 2018 to 2022, while sleep duration continuously decreased. A particularly strong negative relationship between smartphone addiction and sleep duration was found.Conclusion: These results suggest that smartphone addiction is strongly associated with sleep deprivation in children, emphasizing the need for policies and intervention measures to create a healthy sleep environment for children.Keywords: children, sleep duration, smartphone addiction, panel quantile regression analysis, problematic smartphone use, quality of life